Decoupling touch from sex: gender(ed) representations of physical intimacy in the cuddle industry - Santos, Paulo (Frontiers in Sociology, 2023)
In recent years, Europe has witnessed the rise of a new and unconventional type of worker -the professional cuddler. What practitioners offer is a session of non-sexual physical intimacy which, despite efforts to frame the service as a form of therapy, is often misinterpreted as a front for prostitution. As expected from an intimate and embodied kind of labour, workers are largely women who must frequently deal with unwanted sexual advancements. If, on one hand, desexualization strategies in this particular context have the potential to resignify gendered understandings of physical intimacy, on the other hand, they incur in the risk of reproducing and reinforcing those same social representations which they're up against. Drawing from a 3-year online ethnographic study of professional cuddlers and their social world, the present research explores how the representational limbo that practitioners experience could be better understood as a product of the "sexusociety".